Correlates of GLA family adjuvants' activities. (October 2018) - Reed, Steven G.; Carter, Darrick; Casper, Corey; Duthie, Malcolm S.; Fox, Christopher B.
Graphical abstract: Highlights: Research has advanced our understanding of the crude TLR4 agonist LPS to generate suitable adjuvants based on bacterial extraction (MPL) or chemical synthesis (GLA and SLA). Formulation of TLR4 agonists has a significant influence on their in vivo activity. MPL ® is included in several approved vaccines. Several emerging vaccines are using formulations of synthetic TLR4 agonists to enhance immune responses Abstract: Lipopolysaccharide (LPS) is a well-defined agonist of Toll-like receptor (TLR) 4 that activates innate immune responses and influences the development of the adaptive response during infection with Gram-negative bacteria. Many years ago, Dr. Edgar Ribi separated the adjuvant activity of LPS from its toxic effects, an effort that led to the development of monophosphoryl lipid A (MPL). MPL, derived from Salmonella minnesota R595, has progressed through clinical development and is now used in various product-enabling formulations to support the generation of antigen-specific responses in several commercial and preclinical vaccines. We have generated several synthetic lipid A molecules, foremost glucopyranosyl lipid adjuvant (GLA) and second-generation lipid adjuvant (SLA), and have advanced these to clinical trial for various indications. In this review we summarize the potential and current positioning of TLR4-based adjuvant formulations in approved and emerging vaccines.